Proceedings of the Urban Food Systems Policy Forum - CGIAR Initiative on Resilient Cities (CGIAR Initiative on Resilient Cities, 2024)
More than half of Filipinos now live, work, and eat in urban areas, a number expected to rise to 84% by 2050. In these areas, low-income urban residents rely heavily on informal food vendors, who are vital for their food security. Food vending is also an important form of urban employment, particularly for women. Another key source of food security in cities is small-scale food production in backyards and small urban plots, However, informal food vending faces challenges such as limited access to safety information, business support, and policy attention, while local producers struggle with land access, resources, and technology. To address these issues, the CGIAR Resilient Cities Initiative and the Quezon City Government launched the 'Vendor Business School' program to equip vendors with entrepreneurial and food safety skills. The partnership also supported local food production through the Joy of Urban Farming program.